1982
DOI: 10.1093/jn/112.12.2363
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-Induced Changes in Copper and Zinc Metabolism in the Syrian Hamster

Abstract: The temporal response of zinc and copper metabolism to endotoxin administration was examined in Syrian hamsters over a 144-hour period. Serum copper was significantly elevated at 12, 24 and 72 hours after endotoxin, whereas serum zinc was reduced 4-48 hours after treatment. A brief elevation (8 hours) in liver copper concentration and a sustained (72 hours) increase in liver zinc concentration were also observed. The amount of zinc associated with liver metallothionein (MT) progressively increased with time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…This effect of endotoxin may be species-or age-specific. For example, endotoxin administration to Syrian hamsters increased serum Cu concentration but did not decrease Cu concentrations in liver (6). The effects of LPS on the concentrations of Zn and Cu in liver cytosol and the binding of these metals to MT should be examined in context of the changes in Zn and Cu distribution and binding that occur in liver in early postnatal life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect of endotoxin may be species-or age-specific. For example, endotoxin administration to Syrian hamsters increased serum Cu concentration but did not decrease Cu concentrations in liver (6). The effects of LPS on the concentrations of Zn and Cu in liver cytosol and the binding of these metals to MT should be examined in context of the changes in Zn and Cu distribution and binding that occur in liver in early postnatal life.…”
Section: Discussionmentioning
confidence: 99%
“…In rats and Syrian hamsters, endotoxin treatment increases Zn and decreases Cu concentrations in liver and decreases Zn and increases Cu concentrations in plasma (6,7). At the cellular level, endotoxin treatment increases the amount of Zn bound to MT, a cytosolic transition metal-binding protein, in the liver (8) and in cultured hepatocytes (9) and increases the urinary excretion of MT (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of studies has shown metallothionein-bound zinc and copper is responsive to dietary supplies of these nutrients (Richards and Cousins, 1976;Bremner and Davies, 1976;McCormick et aI., 1981;Whanger and Ridlington, 1982). Increased binding of zinc to metallothionein is brought about by food restriction (Bremner and Davies, 1975;Richards and Cousins, 1976), environmental stresses (Oh et al, 1978), infectious agents (Soboscinski et al, 1978), liver regeneration (Ohtake et al, 1978) and endotoxin administration (Etzel et al, 1982). Metallothionein messenger RNA is increased following treatment with zinc (Shapiro et al, 1978;Durnam and Palmiter, 1981 ;McCormick et aI., 1981;Menard et al, 1981;Swerdel and Cousins, 1982), copper (Mercer et al, 1981;Durham and Palmiter, 1981) and cadmium (Anderson and Weser, 1978;Ohi et al, 1981), endotoxin (Etzel et al, 1982), glucocorticoids (Etzel et al, 1979;Hager and Palmiter, 1981) as well as during fetal development (Ouellette, 1982).…”
Section: Function Of Metallothioneinmentioning
confidence: 99%
“…The arrival of Mark Failla, my first postdoctoral associate, allowed us to study the hormonal regulation of zinc and cadmium metabolism under in vitro conditions (13). Charlie McCormick and Ken Etzel joined as postdoctoral associates and worked on induction of MTmRNA as modulated by the dietary zinc level (27) and endotoxin/hormonal control of zinc metabolism (12), respectively.…”
Section: Rutgers Universitymentioning
confidence: 99%